The dynamics and interactions of respiratory pathogen carriage among French pilgrims during the 2018 Hajj - Van-Thuan Hoang; Thi-Loi Dao; Tran Duc Anh Ly; Khadidja Belhouchat; Kamel Larbi Chaht; Jean Gaudart; Bakridine Mmadi Mrenda; Tassadit Drali; Saber Yezli; Badriah Alotaibi; Pierre-Edouard Fournier; Didier Raoult; et al. (Emerging Microbes and Infections, 2019)
ABSTRACTWe conducted this study to describe the dynamics of the acquisition of respiratory pathogens, their potential interactions and risk factors for possible lower respiratory tract infection symptoms (LRTI) among French pilgrims during the 2018 Hajj. Each participant underwent four successive systematic nasopharyngeal swabs before and during their stay in Saudi Arabia. Carriage of the main respiratory pathogens was assessed by PCR. 121 pilgrims were included and 93.4% reported respiratory symptoms during the study period. The acquisition of rhinovirus, coronaviruses and Staphylococcus aureus occurred soon after arrival in Saudi Arabia and rates decreased gradually after days 5 and 6. In contrast, Streptococcus pneumoniae and Klebsiella pneumoniae carriage increased progressively until the end of the stay in Saudi Arabia. Haemophilus influenzae and Moraxella catarrhalis carriage increased starting around days 12 and 13, following an initial clearance. Influenza viruses were rarely isolated. We observed an independent positive mutual association between S. aureus and rhinovirus carriage and between H. influenzae and M. catarrhalis carriage. Dual carriage of H. influenzae and M. catarrhalis was strongly associated with S. pneumoniae carriage (OR = 6.22). Finally, our model showed that M. catarrhalis carriage was negatively associated with K. pneumoniae carriage. Chronic respiratory disease was associated with symptoms of LRTI. K. pneumoniae, M. catarrhalis-S. aureus and H. influenzae-rhinovirus dual carriage was associated with LRTI symptoms. Our data suggest that RTIs at the Hajj are a result of complex interactions between a number of respiratory viruses and bacteria.